2003
DOI: 10.1046/j.1533-2500.2003.03018.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy‐related Increases in Sensory Perception Thresholds Are Not Correlated with Serum Progesterone Levels

Abstract: CPTs are significantly reduced after parturition. However, this reduction does not appear to be significantly correlated with the reduction in serum progesterone levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A significant reduction was demonstrated in sensory perception threshold and pain threshold between the prepartum and postpartum states. 24,25 On the contrary, some other authors reported no modifications in pain threshold during delivery. 26,27 In these studies, tests were performed before and immediately after delivery.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A significant reduction was demonstrated in sensory perception threshold and pain threshold between the prepartum and postpartum states. 24,25 On the contrary, some other authors reported no modifications in pain threshold during delivery. 26,27 In these studies, tests were performed before and immediately after delivery.…”
Section: Discussionmentioning
confidence: 93%
“…As we stated before, a significant reduction was demonstrated in sensory perception threshold and pain threshold between the prepartum and postpartum states. 24,25 So, altered sensory perception thresholds may be the reason for high prevalence of somatic symptoms. Moreover, considering the high rate of FS in pregnant subjects, it may be argued that the majority of the complaints of pregnancy may be the somatic symptoms of coexisting FS in these patients.…”
Section: Discussionmentioning
confidence: 99%